The impact of perinatal trauma and HIV exposure on maternal mental health and infant social-emotional development in Khayelitsha, South Africa. - Motingoe, Kediemetse (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.